Platelet Purinergic Receptors in Thrombosis and Inflammation - Gachet, Christian; Hechler, Beatrice (Hämostaseologie, 2020)
It took approximately 40 years from the seminal identification of adenosine diphosphate (ADP) as the factor R, an agent derived from red blood cells inducing platelet adhesion to glass, to the completion of the repertoire of its receptors on platelets and its importance in haemostasis and thrombosis. ADP, either derived from red blood cells or released by platelets themselves, stimulates platelets via two G protein-coupled receptors, P2Y1 and P2Y12. In addition, adenosine triphosphate, also contained in the platelet dense granules, activates the P2X1 cation channel. Each of these receptors plays a specific role during platelet activation and aggregation, with relevance to haemostasis, thrombosis and various inflammatory processes where platelets are involved including chronic responses such as atherosclerosis or acute responses such as sepsis, endotoxaemia or allergic asthma. Finally, platelets also express P2Y14, a receptor activated by released uridine diphosphate glucose. Although devoid of any known role in haemostasis, this receptor seems to play a specific role in neutrophil chemotaxis.
Keywords: nucleotides; platelets; thrombosis; inflammation; atherosclerosis